PENERAPAN METODE USER CENTERED DESIGN (UCD) PADA APLIKASI BUKU SAKU TKJ BERBASIS ANDROID - Muniroh, Nur; Ariansyah, Awal; Setiawan, Willy (STMIK Komputama Majenang, 2021)
The Buku Saku TKJ application is a tool for vocational students majoring in Computer and Network Engineering (TKJ) to support learning materials in the TKJ major. One of the important parts in creating digital products is to create products that are comfortable for users to use by prioritizing user involvement in the process. User comfort and satisfaction when using a product is very important. Because, then the company can convey the value or use that they need to accept and feel. User Centered Design (UCD) is a process that focuses on the user or users. The purpose of this study is to apply the User Centered Design (UCD) method in making the Buku Saku TKJ application which is expected to meet user needs, resulting in a Buku Saku TKJ application design as a container for TKJ's core material. The results of the first functional test / black-box testing, namely the application can run well with 100% validity test results, meaning that the application has run according to the design that has been tested previously, while the second functional test level of user satisfaction answered